The determinant factors of undulatory underwater swimming performance: A systematic review. Issue 11 (3rd June 2022) - Ruiz-Navarro, Jesús J.; Cuenca-Fernández, Francisco; Sanders, Ross; Arellano, Raúl
ABSTRACT: The prominence of undulatory underwater swimming (UUS) has been clearly observed during recent international events. Improvement of this phase is important for overall performance. The aim of this systematic review was to identify the key factors that modulate UUS performance and provide coaches and sports science practitioners with valuable and practical information to optimise it. PubMed, Web of Science, Scopus, and SPORTDiscus databases were searched up to 14 October 2021. Studies involving competitive swimmers and which included UUS performance assessment were considered. Methodological quality assessment was conducted for the included articles. From the 193 articles screened, 15 articles were included. There was a substantial body of research conducted on kicking frequency, vertical toe and body wave velocity, angular velocity of the joints, distance per kick, joint amplitudes and mobility, and body position in UUS performance. However, further investigation is required for muscle activation and muscle strength influence. The results from this review contribute to understanding of how to optimise UUS performance, identifying the key aspects that must be addressed during training. Specifically, the caudal momentum transfer should be maximised, the upbeat duration reduced, and the frequency that best suits swimmers' characteristics should be identified individually.